IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DI KELAS - Juliaans E R Marantika; Jolanda Tomasouw; Eldaa C Wenno (Universitas Pattimura, 2023)
Differentiated learning is one part of the policy of implementing Merdeka Belajar Curriculum in schools. This learning pattern emphasizes the management of education in heterogeneous classes. In this learning context, teachers are required to be able to design learning activities that can accommodate differences in student characteristics and backgrounds. Implementing differentiated learning without assistance for teachers at school is certainly not easy. This community service activity for the German Language Education Study Program aims to provide knowledge to teachers to design and implement differentiated learning. The results achieved through this activity are teachers have knowledge about the concept and application of differentiated learning. Teachers understand the aspects of differentiated learning that need to be considered in planning, namely content, process, product, and environment or learning climate in the classroom. Teachers can decide how these four elements will be incorporated into classroom learning. Teachers can also customize the learning environment and atmosphere, as well as the content, process and product of each class based on the previously diagnosed student profile. In addition, teachers also understand the indicators that need to be used to assess student learning achievementobtained from various media can be explained properly to avoid the wrong concept